Multiple Cervical Arteries Dissection Associated With Fibromuscular Dysplasia: A Case Report - Julia Goginski; Renato Fedatto Beraldo; Ricardo Nascimento Brito; Gianluca Scalia; Giovanni Federico Nicoletti; Lohana Pompelli Scapatici; Bruno Liebl; Zeferino Demartini Junior; Bipin Chaurasia (Clinical Case Reports)
ABSTRACT Spontaneous cervical artery dissection is a condition often associated with connective tissue diseases, such as fibromuscular dysplasia (FMD), a complex angiopathy primarily affecting medium‐sized arteries. While single‐vessel dissection is more common, simultaneous involvement of three cervical arteries is rare. We present the case of a 30‐year‐old female patient who suffered from bilateral cerebellar infarction, subarachnoid hemorrhage, and hydrocephalus, necessitating external ventricular drainage and posterior fossa decompressive craniectomy. Multimodal imaging, including computed tomography angiography (CTA), magnetic resonance angiography (MRA), and digital subtraction angiography (DSA), confirmed the presence of FMD with dissections involving the right internal carotid artery and both vertebral arteries. Following a two‐month course of antiplatelet therapy, the patient experienced minimal residual symptoms, enabling independent daily activities. Given that FMD is an underrecognized cause of multiple cervical artery dissections, clinicians should maintain a high index of suspicion when encountering such cases. This case highlights the importance of thorough investigation and management in similar clinical presentations.